2004
DOI: 10.1111/j.1440-1819.2004.01265.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in behavioral symptoms and advance of activity acrophase after short‐term bright light treatment in severe dementia

Abstract: Ten elderly subjects with severe dementia were given bright light (5000-8000 lux) for 45 min each morning for 4 weeks. Two rating scales of behavioral symptoms in dementia were used as outcome measures: Cohen-Mansfield Agitation Inventory (CMAI) and Behavior Pathology In Alzheimer's Disease Rating Scale (BEHAVE-AD), a scale for sleep-wake disturbances, and actigraphy to monitor activity rhythm. Behavioral symptoms improved with treatment. No changes in sleepwake measures were found. There was an advance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 19 publications
2
43
1
Order By: Relevance
“…Furthermore, also Skjerve et al [47] did not find significant differences on the variables IS, IV, or RA after a short bright light treatment; in this study, the authors concluded that the short treatment period (i.e., 4 weeks) was not sufficient to influence the circadian rhythm in severely demented patients. Another possible relevant factor influencing the response to light treatment is the season of the year.…”
Section: Resultsmentioning
confidence: 61%
“…Furthermore, also Skjerve et al [47] did not find significant differences on the variables IS, IV, or RA after a short bright light treatment; in this study, the authors concluded that the short treatment period (i.e., 4 weeks) was not sufficient to influence the circadian rhythm in severely demented patients. Another possible relevant factor influencing the response to light treatment is the season of the year.…”
Section: Resultsmentioning
confidence: 61%
“…Morning light therapy also seems to delay the onset of sundowning by an hour and a half, although the ratings of the agitation are not altered (74). Even in severe dementia morning light therapy might lead to phase advances of circadian rhythms and improve behavioral symptoms (75), and both morning and evening light therapy improves circadian parameters and leads to consolidation of sleep (74). Dowling et al (76) did not report beneficial effects of light therapy on sleep parameters in institutionalized AD patients, but the light therapy did lead to a more stable circadian phase, and it has been suggested that those AD patients with the most severe circadian abnormality are most likely to respond to light therapy (77).…”
Section: Chronotherapeutics In Admentioning
confidence: 99%
“…137 The interventions consisted of white broad spectrum light therapy, 2500-5000 137,146 Benefits of treatment are closely balanced with harm/burden. In addition to the general side effects reported in the "Harms and Adverse Effects" section, other side effects in this population range from complaints of eye irritation 138 to agitation and confusion, 141 and these potential drawbacks should be considered when recommending treatment. Furthermore, depending on the method and setting of light delivery, treatment may be labor intensive, and modest improvements in outcomes may not justify associated costs.…”
Section: 44a the Tf Suggests That Clinicians Treat Iswrd In Elderlmentioning
confidence: 99%